PIK3AP1 and SPON2 Genes Are Differentially Methylated in Patients With Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Adenitis (PFAPA) Syndrome - Lovšin, Ema; Kovač, Jernej; Tesovnik, Tine; Toplak, Nataša; Perko, Daša; Rozmarič, Tomaž; Debeljak, Maruša; Avčin, Tadej (Frontiers in Immunology, 2020)
Periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome is the most common autoinflammatory disease in children and is often grouped together with hereditary periodic fever syndromes, although its cause and hereditary nature remain unexplained. We investigated whether differential DNA methylation was present in DNA from peripheral blood mononuclear cells (PBMC) in patients with PFAPA versus healthy controls. A whole epigenome analysis (MeDIP and MBD) was performed using pooled DNA libraries enriched for methylated genomic regions and identified candidate genes, two of which were further evaluated with methylation specific restriction enzymes coupled with qPCR (MSRE-qPCR). The analysis showed that the PIK3AP1 and SPON2 gene regions are differentially methylated in patients with PFAPA. MSRE-qPCR proved to be a quick, reliable and cost-effective method to confirm results from MeDIP and MBD. Our findings indicate that a B cell adapter protein (PIK3AP1), as the PI3K binding inhibitor of inflammation, and spondin-2 (SPON2), as a pattern recognition molecule and integrin ligand, could play a role in the etiology of PFAPA. Their role and impact of changed DNA methylation in PFAPA etiology and autoinflammation need further investigation.